Teatr Polski w Poznaniu za dyrekcji Edmunda Rygiera (1896-1908) - Przybyszewska, Alicja (My University, 2013)
Przedmiotem dysertacji jest historia Teatru Polskiego w Poznaniu dyrekcją Edmunda Rygiera, artysty dramatycznego z Krakowa. Jego dyrekcja w Teatrze Polskim, trwająca 12 lat, była czasem przełomu dla rozwoju lokalnej sceny; nastąpiła wówczas modernizacja repertuaru, poprzez wprowadzenie dramatów naturalistycznych i symbolicznych. Nadto, Rygier doprowadził do przekształcenia prowincjonalnego teatru w przedsiębiorstwo teatralne, przynoszące zyski. Praca doktorska ma dokumentacyjny i analityczny charakter. Dyskurs skupia się na reformach teatralnych dyrektora Rygiera, osadzonych w kontekście ekonomicznej i artystycznej rywalizacji z niemieckim Teatrem Miejskim w Poznaniu. W pierwszej części dysertacji przedmiotem uwagi jest artystyczna droga Rygiera oraz sytuacja sceny poznańskiej przed jego dyrekcją. Druga część dysertacji zawiera prezentację repertuaru Teatru Polskiego na przełomie XIX i XX w. (sztuki dobrze skrojone, dramaty naturalistyczne, historyczne i romantyczne), w celu przedstawienia polityki repertuarowej Rygiera i recepcji wystawionych przez niego sztuk. Do pracy doktorskiej dołączony został aneks, zawierający repertuar Teatru Polskiego z lat 1896-1908, listę artystów zatrudnionych wówczas na scenie poznańskiej oraz indeks wszystkich sztuk, wystawionych w Poznaniu za dyrekcji Rygiera.

The subject of this dissertation is the history of Polish Theater in Poznań under the long-term management of Edmund Rygier, a dramatic artist from Cracow. His management of Polish Theater was an absolute turning-point for the development of the local stage. There are two basic theses of the discourse. Firstly, the new director modernized Polish Theater through the inauguration of modern repertoire: symbolic and naturalistic drama. Secondly, Rygier transformed the provincial stage in Poznań into a theatrical enterprise, which functioned independently and brought profits. PhD dissertation has documenting and analytical character. These studies focused on the director of Polish Theatre and his theatrical reforms. Also there are analysis the context of theTeatru Polskiego w latach 1896-1908 (sztuki dobrze skrojone, economic and artistic rivalry with the German theater in Poznań. In the first part of the dissertation the objects of note are: the artistic position of Rygier and the situation of Polish Theatre before his management. The second part has resulted from description the repertoire of Polish Theatre in the years 1896-1908 (well-made plays; naturalistic, historical and romantic dramas). The purpose was to present the directions of Rygier’s theatrical politics and a reception of the drama presented by him. An appendix has been added, including the repertoire of Polish Theater in Poznań in the years from 1896 to 1908, a list of all dramas presented in Poznań by Rygier and the index of dramatic artists employed in the theater then.
Polish Theater in Poznań under the managment of Edmund Rygier (1896-1908)
Wydział Filologi Polskiej i Klasycznej: Instytut Filologii Polskiej
Keywords: Teatr Polski w Poznaniu; Historia teatru polskiego XIX w.; Edmund Rygier; Polish Theater in Poznań; History of the Polish theater XIXth century